Eastern European Roma: ethnic discrimination in the public healthcare system - Brandon Muncan (Inishmore Laser Scientific Publishing Ltd, 2018)
The term "human rights" describes the inherent, equal, and irrevocable freedoms of the individual, and includes access to the basic necessities of life, freedom of expression, right to justice, and state of peace. Among these rights is access to quality healthcare and medical treatment for chronic and acute illness. In Eastern Europe, the Roma minority experience limitations to the provision of quality medical care as a result of cultural, ethnic, and racial stigma. Such discrimination results from historic sociocultural and economic seclusion across the entire European Romani diaspora, and leads to higher disease incidence and mortality amongst members of this ethnic group. This paper examines some of the barriers Roma face in Eastern European healthcare systems and provides considerations for future social changes to allow all citizens and patients access to equal treatment.